ASYMMETRIC INFORMATION IN AUTOMOBILE INSURANCE: AN OVERVIEW - Chiappori, Pierre-André (Assurances)

(untitled) (HEC Montréal, 1999)
The goal of this paper is to briefly review a number of empirical models that explicitly aim at testing for or evaluating the importance of asymmetric information in automobile insurance. Modern insurance economics has been deeply influenced by the recent developments of contract theory. Our understanding of such crucial aspects as the design of optimal insurance contracts, the form of competition on insurance markets or the role of public regulation, just to name a few, systematically refers to the basic concepts of contract theory—moral hazard, adverse selection, commitment, renegotiation and others. Conversely, it is fair to say that insurance has been, and to a large extend still remains, one of the most important and promising field of empirical application for contract theory.